La Convention des Nations Unies sur les contrats de vente internationale de marchandises : Étude comparative des dispositions de la Convention et des règles de droit québécois en la matière - Samson, Claude (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1982)
On April 11, 1980, the U.N. Diplomatic Conference held in Vienna approved the Convention on contracts for the International Sale of Goods. This paper deals with the most interesting aspects of the Convention, comparing them with the rules of the Civil Code and the Draft Civil Code of Quebec on this matter. The provisions of this international uniform law are quite close to the rules and remedies existing in civil law juridictions. The major differences between the Convention and the Quebec Law are more technical than substantial. The differences between the uniform law and the national law can also be explained by particular circumstances of international trade which require more celerity and security in the field of international business transactions.